2013
DOI: 10.1364/ol.38.004663
|View full text |Cite
|
Sign up to set email alerts
|

Liquid crystal spatial light modulator with very large phase modulation operating in high harmonic orders

Abstract: Unusually large phase modulation in a commercial liquid crystal spatial light modulator (LCSLM) is reported. Such a situation is obtained by illuminating with visible light a device designed to operate in the infrared range. The phase modulation range reaches 6π radians in the red region of the visible spectrum and 10π radians in the blue region. Excellent diffraction efficiency in high harmonic orders is demonstrated despite a concomitant and non-negligible Fabry-Perot interference effect. This type of SLM op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 14 publications
2
11
0
Order By: Relevance
“…9-12). A diffractive profile with m π 2 maximum phase modulation -m being an integer number-operates at higher harmonic orders [13][14][15] and has proved to show interesting properties for achieving an effective reduction of the chromatic aberration that would otherwise affect severely common 1 st -diffractive order lenses. Harmonic diffractive lenses with phase shift being an odd multiple of π (or, equivalently, OPD being an odd multiple of 0 / 2 λ ) also direct light between two neighbor diffraction order images (with 40.5% energy efficiency each).…”
Section: Introductionmentioning
confidence: 99%
“…9-12). A diffractive profile with m π 2 maximum phase modulation -m being an integer number-operates at higher harmonic orders [13][14][15] and has proved to show interesting properties for achieving an effective reduction of the chromatic aberration that would otherwise affect severely common 1 st -diffractive order lenses. Harmonic diffractive lenses with phase shift being an odd multiple of π (or, equivalently, OPD being an odd multiple of 0 / 2 λ ) also direct light between two neighbor diffraction order images (with 40.5% energy efficiency each).…”
Section: Introductionmentioning
confidence: 99%
“…In a previous work [4], the use of LC-SLM devices with extended phase range, i.e., from 0 to 4π, was showed for diminishing artifacts like fringing effects and pointed out the possibility of exploiting this fact to reduce chromatic aberrations. Further, inverted chromatic dispersion for a blazed diffraction grating was also reported [5] by using a very high phase modulation depth SLM which was designed for infrared and operated under visible light. A theoretical chromatic study of other elements, such as axicons or light swords [6], has also been reported in literature by means of diffraction integrals.…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, modern liquid crystal on silicon (LCoS) modulators provide phase-only modulation with larger phase modulation dynamic range that may reach 4π o even 8π for some operating wavelength. These devices are useful to test new designs of first-order, second-order [8] and higher order [9] diffractive optical elements with no need of fabricating them physically, and with the often-stated advantages of flexibility and speed at a reasonable cost. In addition, shadowing effects produced by too high echelettes are overcome when the multiorder diffractive element is implemented by a SLM.…”
Section: Introductionmentioning
confidence: 99%